Regulated cell death mechanisms and their crosstalk with the immune system 1 - Baena-Lopez, Luis Alberto (Henry Stewart Talks, 2020)
Cell death definition, biological and evolutionary significance, Major regulated cell death (RCD) mechanisms, Key secondary messengers in cell death